Students’ perceived restorativeness of university environment: the validation of the Rest@U scale - Menardo, Elisa; Brondino, Margherita; Damian, Ottavia; Lezcano, Marco; Marossi, Camilla; Pasini, Margherita (Frontiers in Psychology, 2024)
University students are likely to encounter mental health issues throughout their educational journey. Among the various factors that can impact students' well-being, the physical environment can potentially restore cognitive, physiological, and emotional resources, thereby enhancing academic performance, and overall quality of life, while reducing feelings of stress and depression. The Perceived Restorativeness Scale is the most commonly used tool to assess the level of restorativeness derived from the educational physical environment. However, a tailored measure could be a more psychometrically suitable approach to capture the context-specific characteristics of university environments for academic students. This study aims to validate an instrument that can accurately evaluate university spaces to measure the perceived restorativeness of university students. A total sample of 685 students from two Italian universities participated in the evaluation of the psychometric properties of the Restorativeness at University scale (Rest@US), consisting of 13 items divided into four dimensions: Fascination, Being-away, Scope, and Coherence. The hypothesized four-factor model (Being-away, Fascination, Scope, and Coherence) demonstrated excellent fit indices in both the calibration and validation samples and was invariant for sex. The scale demonstrates good reliability. Furthermore, criterion validity has been confirmed, highlighting that, in a theoretically consistent manner, the perceived restorativeness of university physical environments from the point of view of students and its dimensions were negatively correlated with techno-overload and study-related workload and positively correlated with perceived performance and psycho-physical well-being.